1989
DOI: 10.1104/pp.91.3.905
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Low Temperature on Respiration and Contents of Phosphorylated Intermediates in Darkened Barley Leaves

Abstract: The aim of this work was to examine the effect of exposure of leaves to low temperatures (5°C) upon the contents of phosphorylated intermediates and respiration in darkened barley (Hordeum vulgare L.) plants which differed in their carbohydrate status. In leaves that had previously been illuminated for 24 hours, there was a large increase in amounts of phosphorylated metabolites at 50C during the first 3 hours of darkness, compared with control plants kept at 30°C. Hexose phosphates accounted for about two-thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
5

Year Published

1992
1992
2010
2010

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 22 publications
2
30
0
5
Order By: Relevance
“…1, inset) and then declined markedly. The reason for this transient rise was not known, though it may be related to carbohydrate metabolism, as suggested by Heichel (11), or increases in Fru-2,6-P2 (17). In contrast, Rn of C album leaves declined immediately after darkening.…”
Section: Respiration Of C3 and C4 Leaves With Different N Contentsmentioning
confidence: 94%
“…1, inset) and then declined markedly. The reason for this transient rise was not known, though it may be related to carbohydrate metabolism, as suggested by Heichel (11), or increases in Fru-2,6-P2 (17). In contrast, Rn of C album leaves declined immediately after darkening.…”
Section: Respiration Of C3 and C4 Leaves With Different N Contentsmentioning
confidence: 94%
“…Photosynthesis at 5~ results in large increases to all hexose-phosphate pools in both CH and NH leaves, except glucose-l-phosphate (GlclP) and UDPGlc in NH leaves. In CH leaves, the increases at saturating PPFDs is particularly pronounced and ranged from ~75-130% for Glc6P, GlclP, Fru6P and UDPGlc to a ninefold increase for Frul,6BP, with the result that total hexosephosphates increased by 120% relative to the levels found at 20~ Previous studies have shown that phosphorylated metabolites accumulate to higher levels after exposure of leaves to low temperatures, and this has been related to low-temperature inhibition of photosynthesis resulting from reduced availability Pi in the stroma (M/ichler et al 1984;Labate and Leegood 1989;Labate et al 1990). However, although the Glc6P/Fru6P ratio of CH leaves at 5~ decreased to around 3 for all PPFDs tested (Table 3), this is still consistent with most of the hexose-phosphates being in the cytosol supporting continued sucrose synthesis.…”
Section: Effect Of Cold-hardening On Metabolite Pools In Conjunc-mentioning
confidence: 97%
“…By contrast, leaves from plants which were low in carbohydrate and hexosephosphate showed no photosynthetic acclimation (Labate and Leegood, 1989). It was suggested that high carbohydrate reserves may potentiate the system for the achievement of high rates of photosynthesis at low temperatures by accumulation of photosynthetic intermediates, such as hexose-phosphate, and that this partially overcomes Pi limitation of photosynthesis (Labate and Leegood, 1989). This interaction between carbohydrate reserves and acclimation to low temperature may also be related to observations that chilling sensitivity in plants such as tomato is partly dependent upon their carbohydrate status (King et al, 1988).…”
Section: Changes In Other Enzymesmentioning
confidence: 72%
“…Primary leaves of barley plants which contained large carbohydrate reserves and high hexose-phosphate showed photosynthetic acclimation to low temperature. By contrast, leaves from plants which were low in carbohydrate and hexosephosphate showed no photosynthetic acclimation (Labate and Leegood, 1989). It was suggested that high carbohydrate reserves may potentiate the system for the achievement of high rates of photosynthesis at low temperatures by accumulation of photosynthetic intermediates, such as hexose-phosphate, and that this partially overcomes Pi limitation of photosynthesis (Labate and Leegood, 1989).…”
Section: Changes In Other Enzymesmentioning
confidence: 96%